2021
DOI: 10.5194/piahs-384-31-2021
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the altimetry-based water levels from Sentinel-3A and B in the Inner Niger Delta

Abstract: Abstract. The comprehension of water level fluctuations and the sustainability of the Inner Niger River Delta (IND) is a major concern for the scientific community, but also for the local population. Located in the centre of Mali, the heart of the Sahel, the delta is characterised by a floodable area of more than 32 000 km2 during the rainy season, which contributes very strongly to the vitality of local ecosystem, and is consequently classified as a Ramsar site under the international Convention for Wetlands.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Between 2018 and 2022, official retrackers from different radar altimetry missions are used in twentyone publications. In five publications [134][135][136][137][138] only data from the Sentinel-3 mission were used and its performance was validated by comparing in-situ gauge data with the altimetry-based water levels. In [134] it is shown that water level variations based on the empirical OCOG [117] retracker are significantly better than the physical Ocean [122] method.…”
Section: Official Retracking Algorithmsmentioning
confidence: 99%
“…Between 2018 and 2022, official retrackers from different radar altimetry missions are used in twentyone publications. In five publications [134][135][136][137][138] only data from the Sentinel-3 mission were used and its performance was validated by comparing in-situ gauge data with the altimetry-based water levels. In [134] it is shown that water level variations based on the empirical OCOG [117] retracker are significantly better than the physical Ocean [122] method.…”
Section: Official Retracking Algorithmsmentioning
confidence: 99%
“…The most widely used multitemporal and multispectral satellite observations for this purpose are derived from Landsat (LS) [7][8][9][10], Sentinel [11][12][13], Moderate Resolution Imaging Spectroradiometer (MODIS) [6,[14][15][16], and SPOT (Satellite Pour l'Observation de la Terre) [17,18]. Much of the available literature on water-body extraction focusses on one type of water body (e.g., lakes, rivers, etc.)…”
Section: Introductionmentioning
confidence: 99%